PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK MELALUI PENDEKATAN PEMBELAJARAN MENDALAM DI SEKOLAH DASAR - Nana Harlina Haruna; Abdul Latif Salam (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to examine the effectiveness of the deep learning approach in strengthening character education for elementary school students. The background of the problem is the challenge of implementing character education effectively, where content-centered learning often fails to internalize moral values in students. Deep learning is seen as a potential solution because this approach encourages holistic, reflective, and applicable understanding, rather than mere memorization. This study uses mixed methods with an explanatory sequential design, in which quantitative data is collected and analyzed first, followed by qualitative data to deepen the findings. The research sample consisted of teachers and students from SDN Sangir Makassar. Quantitative research results showed a significant increase in student character education scores in the experimental group that implemented deep learning, compared to the control group. Qualitative results from interviews and observations supported these findings, showing that deep learning such as collaborative projects and discussions encouraged interaction, problem solving, and deep reflection among students. Overall, this study concludes that the deep learning approach has proven to be effective and significant in strengthening character education, transforming it from theory into a meaningful and sustainable life experience.